A short overview of Clostridium perfringens: Relevancy, Toxinotypes, Clinical Impacts, and the Challenges of Biofilm Formation - Mara-Georgiana Haralambie; Alina Țărnă; Aurelia Coroian; Ana-Maria-Cristina Imbrea; Igori Balta; Lavinia Ștef; Nicolae Corcionivoschi (Scientific Papers Animal Science and Biotechnologies)
C.perfringens, a ubiquitous bacterium, is implicated in a series of recent outbreaks across Europe, reflecting its significance in public health. The organism manifests different clinical presentations in both human and animal hosts. In the realm of veterinary science, its pathogenesis in species such as poultry, cattle, swine, and equines is of particular concern due to the economic implications stemming from morbidity and mortality rates. The enterotoxins produced by this bacterium is the primary cause of symptoms like watery diarrhea, abdominal pains, and cramps in humans, and leads to conditions such as clostridial myonecrosis and necrotic enteritis in animals. An important aspect of its virulence strategy is its ability to form biofilms. These sophisticated microbial assemblages confer an augmented resistance against environmental challenges and antimicrobial interventions. This review consolidates information about C. perfringens outbreaks in Europe, mode of infection, pathogenesis in various animals, associated clinical symptoms, and the nuances of its biofilm formation. The present literature synthesis could provide valuable insights for forthcoming preventive and therapeutic initiatives.